Pathogenicity of Meloidogyne incognita (Kofoid & White) Chitwood on Matricaria chamomilla L. - KUMAR, RAKESH PANDEY, H N SINGH, S (Journal of Spices and Aromatic Crops, 1999)
Experiments conducted to ascertain the pathogenicity of Meloidogyne incognita and its effect on growth and flower yield of Matricaria chamomilla under glasshouse conditions indicated that an increase in the initial inoculum level of M. incognita reduced fresh and dry root and shoot weight and flower yield with corresponding decrease in nematode multiplication rate and increase in root-knot indices.